Effect of Blending Ratio and Injection Timing on Combustion and Emissions of a Common-Rail Diesel Engine Fueled by Iso-Propanol-Butanol-Ethanol (IBE) and Conventional Diesel - Ilcin, Kudbettin; Firat, Mujdat; Altun, Sehmus; Okcu, Mutlu (Gazi Univ, 2023)
In present study, combustion characteristics of mixtures of isopropanol-butanol-ethanol (IBE) with petroleum-based diesel fuel at the rates of 10%, 20% and 30% volumetrically in a single-cylinder CRDI engine were examined under different loads which correspond to 20%, 40% and 60% of maximum torque. The effect of the injection timings from 15 degrees CA to 23 degrees CA (bTDC) with 2 degrees CA increments was also studied at 60% load and constant speed of 2400 rpm. Experimental results showed that IBE blends with diesel fuel delayed the combustion at low load while increasing load reduced this delay when compared with diesel fuel. An increase in cylinder gas pressure up to 5.7% and rate of heat release up to 42% in using IBE was observed. Regarding emissions, despite no significant change in CO emission was observed with the load and IBE ratio; UHCs increased up to 35% at low load conditions; however, they reduced at 60% load. While smoke opacity reduced up to 64% with IBE30 when compared with diesel fuel, NOx emissions increased about 10%. The decrease in injection advance caused a decrease in pressure and heat release rate, while NOx emissions increased gradually up to 54% with increasing injection advance.
Keywords: Isopropanol-butanol-ethanol (IBE); emissions; injection timing; common-rail